ANALISIS FATWA DSN MUI No. 131 TAHUN 2019 TENTANG SUKUK WAKAF DARI PERSPEKTIF MAQASHID SYARIAH AL SYATIBI : Analysis of DSN MUI FATWA No. 131 of 2019 Concerning Waqf Sukuk From The Perspective of Al Syatibi’s Maqashid Sharia - Qathrunnada, Elissa; Ghazali, Muhammad Lathoif (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2023)
The potential of waqf in Indonesia is vast, but it has not been matched by the maximization of more productive management in the era of increasing Islamic financial growth. This opportunity is the background for the emergence of investment instruments in the form of sukuk waqf as an effort to maximize the potential of waqf. Provisions and restrictions related to sukuk waqf in Indonesia refer to DSN-MUI Fatwa No. 131 of 2019, so this study aims to analyze the concept of sukuk waqf in DSN-MUI Fatwa No. 131 of 2019 based on Al-Syatibi's Maqashid Syariah perspective using the Systematic Literature Review (SLR) method. The results of this study indicate that through optimizing the utilization of Waqf Linked Sukuk is one of the concrete steps to protect religion, protect the soul, improve the quality of human resources, the formation of future generations of the nation that will have an impact on society through infrastructure networks, and is expected to be maximized to overcome poverty